Examining regional sustainable development policies of selected EU member state - Boateng, George Baafi (Univerzita Pardubice, 2024)
Implementation of Sustainable Development Strategies has gained prominence during the last two (2) decades. Human activities in the bid to achieve economic growth and to earn livelihoods for themselves and dependent relations have had serious effects and implications on the environment either consciously or unconsciously thereby leading to depletion of both renewable and non-renewable resources alike. Human actions have affected the natural ecosystem and have resulted in climate change, rapid depletion of natural endowments and continuous damage to the biodiversity which had tremendous negative impact on the economic, social, and environmental aspects of development. This thesis seeks to identify the pillars of sustainable development and the relationship between TBL and sustainability in the context of regional growth and development. The study found that both countries adopted the TBL framework and the SDGs, but had different approaches, challenges, and outcomes.
Zkoumání regionálních politik udržitelného rozvoje: Případ Rumunska a Švédska
Keywords: sustainability; TBL framework; pillars of sustainable development; development policies; Romania and Sweden; udržitelnost; rámec trojí zodpovědnosti; pilíře udržitelného rozvoje; rozvojové strategie; Rumunsko a Švédsko